Selección de 12 líneas avanzadas F5 de arroz (Oryza sativa L. ssp japonica x Oryza rufipugon G), sometidas a alta salinidad en el cantón Babahoyo - MACIAS MOREIRA, JUAN JOSÉ (2019)
This experimental work was carried out at the greenhouse level on the grounds of the experimental farm "San Pablo", of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km. 7.5 of the Babahoyo - Montalvo highway, with geographic coordinates 476003.18 of Latitude South and 8829743.10 UTM of Longitude West. The land is at an altitude of 8 meters above sea level, humid tropical climate, average annual temperature of 25.7 ℃, average annual rainfall of 1845 mm and relative humidity of 76%. As planting material, 12 advanced F5 lines of rice (Oryza sativa L. ssp japan x Oryza rufipugon G) plus parental lines (JP002, JP003 and Puyón) and a commercial variety (SFL-011) were used. The study factor was Select and characterize advanced lines (F5) of rice, expressing salinity tolerance in segregating populations from Interspecific crosses (Oryza sativa L. ssp japan x Oryza rufipogon G), two levels of salinity were used the level salinity 1 (0.8 dS / m) and salinity level 2 (7.0 dS / m). with a “completely random” design with factorial arrangement (A x B) with six repetitions. Factor A corresponds to 2 levels of salts, factor B at 16 treatments (12 F5 lines of rice, 3 parental and a commercial variety SFL-11). In this study the statistical analysis of the different variables was performed, which were submitted to the analysis of variance (ANOVA) and the Tukey 5% test to determine the statistical significance and to compare the values of the variables studied. For the realization of this study, several agronomic works were carried out such as: preparation of the greenhouse, seedbed, planting, irrigation, weed control, phytosanitary control, fertilization, harvest. In irrigation, a sheet of water was placed from the transplant until the spike was emitted, using grain salt dissolved in the water, in order to maintain the level of 7.0 EC in the salt treatments and a bluelab measuring device was used to guarantee the level of salinity. For the selection of saline tolerant rice F5 lines, the results of the following variable were used in order to compare salinity level 1 (0.8 dS / m) and salinity level 2 (7.0 dS / m) , where the analysis of variance indicates that there is statistical significance, in the variables; number of panicles per plant, grains per panicle, sterility percentage, yield grams plant, this indicates that salinity level 2 (7.0 dS / m), have a negative effect on yield, based on these results it was concluded that the F5 lines of Puyón rice / JP003 P11-10 P: 31 I: 15, Puyón / JP003 P11-10 P: 6 I: 16 were tolerated by salinity level 2 (7.0 dS / m)